Probiotics and prebiotics in the elderly - Hamilton-Miller, J M T (Postgraduate medical journal, 2004)
Probiotics (usually lactobacilli and bifidobacteria) and prebiotics (non-digestible oligosaccharides) have been shown to be useful in preventing certain disease conditions as well as possibly promoting specific aspects of health. In the present review, the evidence from clinical trials for benefits from probiotics and prebiotics to elderly populations is presented and discussed, specifically in respect of three common conditions found in the elderly. Both probiotics and prebiotics may be helpful in malnutrition, particularly in lactose intolerance and calcium absorption, and in constipation. Probiotics have been shown clearly to boost immunity in the elderly, but the clinical significance of this remains to be clarified. These results are encouraging, and further large scale studies seem justified to establish the place of probiotic and prebiotic supplements in elderly subjects.